Rethinking the thrive of Labor Constitution in China. (5th December 2019) - Yan, Tian
ABSTRACT: Labor Constitution is an expression of the interplay between 'Labor' and the 'Constitution'. 'Labor' is usually regarded as a section or field of society. It also serves as a legal system, the spirit of which runs through the Constitution, hold up to the structure of the Constitution, and manifest the very nature of the Constitution. At the same time, it is also found to lay a logical foundation thereof. Those three kinds of relationships co-exist in China, while the second one distinguishes itself from those in the US and therefore constitutes a distinctive national characteristic. When we further look into the perspective relating to the instrumental value of Labor Constitution, five goals are laid out: livelihood, democracy, equality, honor and effectiveness. Although the Labor Law tends to consider itself to be a handy implementation of the Constitution, it still requires some fine-tuning. One can hardly say that it has already satisfied the role as a supporter of the constitutional values, and that's why we found the Labor Constitution in China did 'rise', but has yet to 'thrive'. There are multiple steps to take in order to promote the future development of China's Labor Constitution: give full play to the existing laws as a carry-out of the Constitution, enact new laws accordingly for further and better implementation, and figure out a set of systematic rules regarding Constitution interpretation with an eye to the future.